Od štylistických reflexií K. Hausenblasa k reflexiám o inkluzívnosti štýlu a štylistiky pre societu digitálnej éry - Oľga Orgoňová; Alena Bohunická (Acta Universitatis Carolinae: Philologica)
In the study we reflect the impulses from the work of the Czech stylist K. Hausenblas (1923–2003). In continuity with his stylistic ideas about the variability of ways of constructing discourses in a national language based on the principle of unity in multiplicity, we reflect the concurrent and subsequent thoughts about the pragmatization of stylistics (e.g. in the optics of J. Kořenský or J. Hoffmannová), as well as thoughts about the interactivity of dialogues as presented by J. Kraus, and in the pragmatized concept of communication of Schulz von Thun, enriched by the ideas of J. Dolník. Hausenblas’s ideas about expression style and the variability of its forms with the use of the “offer” of the whole national language are consistent with our ideas about the communicative style of the 21st century as a mode of flexible verbal and nonverbal, culturally and contextually anchored behaviour. After outlining how the focus of theoretical interest after the communicative-pragmatic turn in stylistics shifts from the compositional aspect and the process of speech production to the socio-cognitive aspect, we profile the framing contours of inclusive stylistics in the service of the civil society of the digital era.